Specific alterations in the circulating levels of the SIRT1, TLR4, and IL7 proteins in patients with dementia - Yildiz, Gulsen Babacan; kılıç, Ulkan; ELİBOL, BİRSEN; Elibol, BİRSEN; UYSAL, ÖMER; Uysal, Omer; Kilic, Ertugrul; Yulug, Burak; Sakul, Arzu Sayin; BABACAN YILDIZ, GÜLSEN (My University, 2018)
Sirtuins have gained considerable attention as epigenetic regulators for slowing aging and age-related disorders. The growing association between neurodegeneration and inflammation has led researchers to investigate interactions of sirtuins with inflammatory markers in neurodegenerative diseases. We analyzed SIRT1-s association with chronic inflammation in dementia as an age-related neurodegenerative condition through Toll-like receptor 4 (TLR4) and interleukin-7 (IL7) for the first time. In the present study, we observed a significant increase in the level of SIRT1 in patients with all types of dementia. Interestingly, the level of TLR4 protein was significantly lower in only the patients with Alzheimer-s disease (AD) compared to the healthy elderly subjects. There was no significant change in the level of IL7 between the diseased and healthy elderly subjects. A significant positive correlation between SIRT1 level and age in healthy elderly subjects was evident according to Pearson-s correlation test. However, this correlation was not observed in the dementia patients. Furthermore, the positive correlation between the levels of IL7 and TLR4 in the healthy elderly subjects was absent in the dementia patients. However, there was no direct association between the examined single nucleotide polymorphisms (SNPs) and dementia at the molecular level. According to logistic regression analysis, dementia risk increases 1.16 times due to an increase in the SIRT1 level and 24.23 times due to a decrease in the TLR4 level. Interestingly, a high level in the total antioxidant status (TAS) increases the risk of dementia approximately 33.32 times. Therefore, the current study, for the first time, provides a much better molecular understanding of the interaction between decreasing TLR4 levels and increasing SIRT1 levels in dementia, especially in AD. Furthermore, it highlights the importance of epigenetics in several age-related diseases and suggests that developing novel therapies to prevent or slow down the progression of dementia may support healthy aging.